Genetic Parameters, Correlation and Stability Analysis of Aromatic Rice Landraces of Nepal - Tiwari, Dev Nidhi; Pandey, Madhav Prasad; Bhusal, Tej N; Manandhar, Hira Kaji (Journal of Nepal Agricultural Research Council, 2024)
Rice is the major food crop directly related to the livelihood of majority of rural people in Nepal. Aromatic rice is one of the fundamental groups that has great significance from the nutritional and market point of view all over the world. The main objective of this study was to emphasize on the determination of major genetic parameters, genotypic and phenotypic correlations, stability analysis for yield and major quantitative traits of aromatic rice landraces. Altogether 30 aromatic rice landraces were considered in this study and that were evaluated in three locations namely Hardinath, Tarahara and Khajura with three replications. Two years of multilocation data on nine morphological traits were collected and evaluated. The genetic parameters like genetic variance, phenotypic variance, genotypic coefficient of variation, phenotypic coefficient of variation, heritability and genetic advance were estimated using the statistical methods. The highest GCV and PCV was exhibited by grain yield (23.67 and 25.7) whereas lowest GCV and PCV was found in panicle length (4.9 and 5.6) respectively. Heritability of various traits was measured from 0.76 to 0.98 where the lowest heritability was observed in panicle length and the highest was observed in both heading and maturity days. The genetic advance as percentage of means value ranging from 8.8 to 45 representing panicle length and grain yield respectively. The genetic correlation of the measured traits showed highly significant positive correlation of heading days with maturity (r=1.0004**) and straw yield (r=0.787**) as well as correlation of maturity days with straw yield (r=0.79**). In case of phenotypic correlation, highly significant positive correlation of heading days with maturity (r=0.99**) and straw yield (r=0.7611**) was obtained however there is negative but significant correlation with tillers per meter square (r=-0.296*), filled grain weight (r=-0.305*), 1000 grain weight (r=0.3115*) and grain yield (r=-0.4*). According to the stability analysis, Gouriya and Karia Kamod (bi=1.1) were found more stable. Based on the value of coefficient of determination (R2), most of accessions; Lalka Basmati, Sugandhit Dha-1, Suhpat, Gouriya, Bayerni Masino, Kalo Nunia, Balamsari Dhan, Tilki, Tulsiful and Sunaulo Sugandha were obtained stable in all the three locations in both years. Based on the Superiority Measure (Pi), Samba Masuli Sub-1 and Sugandhit Dhan-1 showed lower Pi values of 132556.16 to 377994.35 hence identified as most stable varieties. This study identified the genetic parameters that provides the useful information for breeding of rice varieties, correlation among the major traits and stability of some aromatic landraces Gouriya and Karia Kamod obtained in all the environments. Thus, findings of this study are highly helpful for future studies to identify desirable traits and genotypes in the further varietal development works in coming days.